The enhanced drought tolerance of rice plants under ammonium is related to aquaporin (AQP). (May 2015) - Ding, Lei; Gao, Cuimin; Li, Yingrui; Li, Yong; Zhu, Yiyong; Xu, Guohua; Shen, Qirong; Kaldenhoff, Ralf; Kai, Lei; Guo, Shiwei
Highlights: Ammonium nutrition increase rice plants drought tolerance more than nitrate nutrition. Drought stress significantly stimulated rice plant root growth under ammonium nutrition. Root AQP expression, activity and root hydraulic conductivity were increased in rice plant supply with ammonium under drought stress. AQP affected rice roots growth and development and drought tolerance. Ethylene accumulation inhibited root growth in rice plant supply with nitrate under drought stress. Abstract: Previously, we demonstrated that drought resistance in rice seedlings was increased by ammonium (NH4 + ) treatment, but not by nitrate (NO3 − ) treatment, and that the change was associated with root development. To study the effects of different forms of nitrogen on water uptake and root growth under drought conditions, we subjected two rice cultivars (cv. 'Shanyou 63' hybrid indica and cv. 'Yangdao 6' indica, China) to polyethylene glycol-induced drought stress in a glasshouse using hydroponic culture. Under drought conditions, NH4 + significantly stimulated root growth compared to NO3 −, as indicated by the root length, surface area, volume, and numbers of lateral roots and root tips. Drought stress decreased the root elongation rate in both cultivars when they were supplied with NO3 −, while the rate was unaffected in the presence of NH4 + . Drought stress significantly increased root protoplast water permeability, root hydraulic conductivity, and the expression of root aquaporin (AQP) plasma intrinsic protein (PIP) genes in rice plants supplied with NH4 + ; these changes were not observed in plants supplied with NO3 − . Additionally, ethylene, which is involved in the regulation of root growth, accumulated in rice roots supplied with NO3 − under conditions of drought stress. We conclude that the increase in AQP expression and/or activity enhanced the root water uptake ability and the drought tolerance of rice plants supplied with NH4 + .